2015
DOI: 10.1159/000441822
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Hepatocellular Cancer

Abstract: Background: Hepatocellular carcinoma (HCC) significantly contributes to the global burden of cancer. Liver cancer is the third most frequent cause of cancer-related death with HCC representing more than 90% of primary liver cancers. The majority of patients are not only affected by the malignant disease but do also suffer from chronic liver disease. Therefore, several factors impact on the prognosis of patients with HCC, including tumor-related factors, liver function and patient-related factors such as perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
0
26
0
3
Order By: Relevance
“…For example, hepatic albumin biosynthesis is downregulated by pro-inflammatory stimuli as part of a negative acute phase reaction in patients with malignancy [ 23 ]. Previous studies have demonstrated the independent prognostic value of hypoalbuminemia in HCC [ 24 , 25 ], and a prospective clinical study revealed malnutrition as an independent negative prognostic risk factor in HCC patients [ 26 ]. Accordingly, numerous studies have also shown better recurrence-free survival (RFS) and OS after curative treatment of HCC if the nutritional status was optimized before treatment by supplementation of branched-chain amino acids [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, hepatic albumin biosynthesis is downregulated by pro-inflammatory stimuli as part of a negative acute phase reaction in patients with malignancy [ 23 ]. Previous studies have demonstrated the independent prognostic value of hypoalbuminemia in HCC [ 24 , 25 ], and a prospective clinical study revealed malnutrition as an independent negative prognostic risk factor in HCC patients [ 26 ]. Accordingly, numerous studies have also shown better recurrence-free survival (RFS) and OS after curative treatment of HCC if the nutritional status was optimized before treatment by supplementation of branched-chain amino acids [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In older in-patients, malnutrition is associated with poor clinical outcomes, including impairment in quality of life, performance status, immune function and liver function, as well as decreased survival. Several studies 5 7 reported a relationship between preoperative nutritional status and poor prognosis in HCC patients. However, the correlation between preoperative nutritional status and prognosis in elderly patients with HCC remains unclear and deserves investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional status of patients is of great importance for their performance status and the tolerance of anticancer therapy. 27 Malnutrition has been identified as an independent predictor for poor diagnosis of HCC. 28 In the current study, patients with advanced and terminal cancers frequently had cachexia, which consumed a large amount of nutrients and could be the reason why we did not detect the beneficial role of a healthy diet among patients with advanced and late TNM stages.…”
Section: Discussionmentioning
confidence: 99%